Effectiveness of New Natural Fibers on Damage-Mechanical Performance of Mortar - Garcia-Herrera, C (Elsevier Ltd, 2017)
Addition of fibers to cement-based materials improve tensile and flexural strength, fracture toughness, abrasion resistance, delay cracking, and reduce crack widths. Natural fibers have recently become more popular in the construction materials community. This investigation addresses the characterization of a new animal fiber (pig hair), a massive food-industry waste worldwide, and its use in mortars. Morphological, physical and mechanical properties of pig hair are determined in order to be used as reinforcement in mortars. A sensitivity analysis on the volumes of fiber in mortars is developed. The results from this investigation showed that reinforced mortars significantly improve impact strength, abrasion resistance, plastic shrinkage cracking, age at cracking, and crack widths as fiber volume increases. Other properties such as compressive and flexural strength, density, porosity and modulus of elasticity of reinforced mortars are not significantly affected by the addition of pig hair. © 2017 Elsevier Ltd